DUKUNGAN SOSIAL TENTANG EFIKASI DIRI MENYUSUI PADA IBU NIFAS - Cemara, Agnes Julisca; Wisuda Andeka Marleni, Ratna Dewi, (JURNAL MEDIA KESEHATAN, 2018)
Bengkulu City is the city with the lowest coverage of 9 districts / cities inBengkulu Province in 2015 by 38%. The success of breastfeeding can be increased inmothers who have high breastfeeding self-efficacy. One of the factors that influencebreastfeeding self-efficacy is the existence of social support sourced from the family(husband), cadres, and health personnel (midwives). This study aims to determine theanalysis of social support on breastfeeding self-efficacy of postpartum in the WorkingArea of PuskesmasLingkar. This research uses qualitative method with phenomenologyapproach. The subjects of the study were chosen by using purposive sampling techniqueconsisting of 6 primary informants which is 3 postpartum mothers with high efficacy and3 postpartum mothers with low efficacy and 6 secondary informants which is 2 midwives,2 cadres and 2 husbands, each consisting of low and high efficacy. The results showedthat social support in the form of family support (husband), cadres and health workers(midwives) affects self-efficacy of breastfeeding in postpartum. Forms of family support(husband) and health personnel (midwife) are informational, emotional, assessment andintrumental support. Forms of cadre support is just informational suppor. It is expectedthat health workers can provide a comprehensive extension of ASI to mother and family.Training of cadres also needs to be done to improve the role and task of cadres inimproving the success of postpartum mother to breastfeed her baby exclusively.